Evaluation of satisfaction of tourists the quality of tourism services based on Kano model and SERVQUAL (Case Study: Tehran Darband area catering units) - Jamileh Tavakolinia; Mostafa Haraeeni (تحقیقات کاربردی علوم جغرافیایی)
Tourism quality is important factor so that influence in return of tourists. Hence, it needed to be developed tourism quality due to stimulate domestic and foreign investment, increase business, and improve economic and social conditions. This study has an applied perspective relevant to type, and has an analytical approach pertaining to descriptive method. Using a questionnaire and taking the reliability of the data into account, the Cronbach’s alpha coefficient (0.834) and content validity, the data and required information were collected; and analyzing the number of 354 forms referring to the Darband restaurants were performed, with respect to documentary research and fieldwork in the sample tests. Based on facts collected due to satisfy consumptions; we found some gaps including, the widest gap of QoSs is relevant to tangibles with average distance -0.33, and narrowest gap of QoSs is pertaining to responsiveness with average distance 0.34. In next step, using Kano model we categories’ QoSs, and the results, based on customers’ respond, shown that 6 features categorized as “attractive,” 5 features categorized as “one-dimensional,” 6 features categorized as “necessary,” and 2 features as rest of 19 characteristics categorized as “unconcerned.” Eventually, according to the findings performed an inspection due find out about a relation over the Spearman correlation, and education, and income.